Exploration of resilience in midwifery students - Argaheni, Niken Bayu; Perestroika, Grhasta Dian; Syarifah, Syarifah (Alma Ata University Press, 2023)
Background: Resilience is considered a vital characteristic and has gained attention in midwifery practice and education. In particular, midwifery students face challenges during their education in both the academic and clinical components of the program. The clinical component of midwifery education is equally demanding. Students work in actual healthcare settings, providing care to expectant mothers and infants. They face the emotional and physical demands of long hours, the need for excellent communication skills, and exposure to complex clinical situations. Resilience enables them to stay composed in high-stress situations and learn from both successes and failures.Objectives: to offer a complete picture of the recent research on the resilience of midwifery studentsMethods: This study's methodology is a scoping review using the prism-ScR checklist, the Joanna Briggs Institute (JBI) critical appraisal tool, and a PEOs framework. It makes use of four databases— Google Scholar, PubMed, Scopus, and ProQuest —and its inclusion criteria are original English articles that can be accessed in full text between 2019 and 2023.Results: Out of 168 publications, we found 10 that are pertinent to the research goals. Qualitative research, cross-sectional studies, and mixed methods studies make up the research. The mapping result includes four themes: Caring, Support, Bounce back, Critical Reflective Skills, A Mandatory skill set, and Burnout.Conclusions: Empathy, resilience, professional identity, perceived concern from peers, and recognition of caring as a prerequisite for the midwifery profession were factors strongly associated with humanistic caring ability. These factors should be incorporated into the midwifery education agenda for agents of change. Facilitating the improvement of empathy, resilience, and professional identity will require strategic training, reinforcement, and transformative educational approaches from educators.